2018
DOI: 10.1172/jci120401
|View full text |Cite|
|
Sign up to set email alerts
|

Ubiquitin ligase RNF8 suppresses Notch signaling to regulate mammary development and tumorigenesis

Abstract: The E3 ubiquitin ligase RNF8 plays critical roles in maintaining genomic stability by promoting the repair of DNA double-strand breaks (DSBs) through ubiquitin signaling. Abnormal activation of Notch signaling and defective repair of DSBs promote breast cancer risk. Here, we found that low expression of the full-length RNF8 correlated with poor prognosis for breast cancer patients. Our data revealed that in addition to its role in the repair of DSBs, RNF8 regulated Notch1 signaling and cell-fate determination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…The ubiquitin E3 ligase RNF8, which primarily functions in transducing DSB signals by conjugating ubiquitin to histones [22], has been reported to participate in tumorigenesis because RNF8 knockout mice develop various tumors spontaneously [44][45], indicating a negative role of RNF8 in tumorigenesis. However, RNF8 appears to have the opposite effect in tumor progression according to recent studies, because it promoted breast cancer proliferation and metastasis by affecting the Wnt/β-catenin pathway and activating the activity of transcription factors such as Twist and ERα [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquitin E3 ligase RNF8, which primarily functions in transducing DSB signals by conjugating ubiquitin to histones [22], has been reported to participate in tumorigenesis because RNF8 knockout mice develop various tumors spontaneously [44][45], indicating a negative role of RNF8 in tumorigenesis. However, RNF8 appears to have the opposite effect in tumor progression according to recent studies, because it promoted breast cancer proliferation and metastasis by affecting the Wnt/β-catenin pathway and activating the activity of transcription factors such as Twist and ERα [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that RNF8 suppressed mammary tumorigenesis [8] (figure 2). The loss of RNF8 in female mouse mammary epithelium cells (MECs) caused spontaneous mammary tumors in mice.…”
Section: Tumorigenesis and Cancer Progressionmentioning
confidence: 98%
“…Genomic instability is known as a pivotal cause of tumorigenesis [64]. Furthermore, female mice with deficiency of RNF8 in MECs exhibit spontaneous mammary tumors, since the loss of RNF8 results in impaired DSB repair and sustained activation of Notch signaling [8]. These findings indicate that RNF8 probably protects against tumorigenesis in some contexts.…”
Section: Conclusion Remarks and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify UBLs that contribute to the etiology of PDA, we queried the TCGA database for UBLs differentially expressed in cancer, including melanoma 27,30 , ovarian cancer 31 , breast cancer [32][33][34] , colorectal cancer 35,36 , lung cancer 37 , and head and neck cancer 36,38 . Of the UBLs that were altered in pancreatic cancer ( Fig S1A) we selected UBLs whose expression may be linked with survival.…”
Section: The Ubiquitin Ligase Rnf125 Is Differentially Expressed In Tmentioning
confidence: 99%